Rancang Bangun Game Stickman Dengan Metode Quadtree - Rico Fernando; Jusia Amanda Ginting (Institut Seni Indonesia Yogyakarta, 2023)
Quadtree method is a method of dividing region into 4. Quadtree method can be applied to make collision detection easier for collidable objects. Collision detection will be done in the smallest region of the quadtree division because of the limited speed in collision detection. This problem becomes a problem where to produce a game with optimal detection is done by dividing the region with quadtree method by dividing the region into 4 until the collidable objects in each region does not exceed the predetermined limits, thus reducing the parts that need to be checked without having to check as a whole. The method used in development is quadtree. This method is suitable to be applied to games that require collision detection in it. From this study it is obtained that the quadtree method by limiting the collision detection area can produce an optimal speed seen from the frame per second produced. The game built is expected to be able to optimize similar games that use collision detection in it. It is suggested to do further research with various types of other games.